HUBUNGAN KECANDUAN GAME ONLINE CLASH OF CLANS TERHADAP PRESTASI AKADEMIK MAHASISWA ILMU KOMUNIKASI FAKULTAS ILMU SOSIAL DAN POLITIK UNIVERSITAS RIAU - Saputra, Rahmadi; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Students are part of society and the academic community needs to be prepared with advances in technology, especially new media era, so that students are able to use the media intelligently and effectively. The new media should be mandatory knowledge that must be overcome by every student, especially students of the University of Riau. Online game Clash of Clans is a game that can be accessed by many players, in which the machines are used for players connected by a networkHowever, because the online game Clash of Clans is puz online games played on smartphones, making it easier for the players to play this game anywhere and anytime, as well as requiring the duration of playing long enough to complete the game online game Clash of Clans, then there the possibility that the online game clash of Clans is an addiction for his players.The concept of the theory that the researchers use a dependency theory. Media System Dependency Theory getting someone drape needs to be satisfied by the use of the media, the more important the role of the media in people's lives, so the greater the influence the media. J. BaranThis research is an explanatory Quantitative Survey. To measure the force between two variables, are addicted to online games Clash of Clans as independent variables and academic achievement as the dependent variable, used product moment correlation, or often called simple correlation.From the calculation results obtained by value thitung0,786 with a probability level of 0.000. Therefore, the probability level <0.05 then it means there is no correlation Addiction Game COC to student academic achievement.Keywords: Kencanduan Online Game and Achievement